Neopentecostalismo: uma interpretação a partir da Teoria da Prática - Fabio Lanza; Edson Elias de Morais; Flávio Braune Wiik (Ciências Sociais Unisinos)
This article aims at presenting the contributions of the Theory of Practice in relation to the historical-anthropological analysis in relation to social change, with emphasis on Protestantism and the Neo-Pentecostalism. Given the fact that religion is made up of people, who follow already established structures, it is assumed that religion simply serves to replicate a given social order. However, out of the Theory of Practice, it is possible to rethink this relationship, and, as already pointed out by Max Weber, religion can be understood as a mechanism of social and cultural transformation from hegemonic forces linked to everyday life and people’s will. The relevance of the Theory of Practice to the study of religion lies in proposing an analysis that considers the cultural and structural issues as well as the practice of individuals who can reframe values and symbols, a factor that in long-term produces structural and cultural change.